Резорбция корней зубов при ортодонтическом лечении (Эндодонтия Today)
The condition of roots of a second teeth is studied at orthodontic treatment. Applied radiographic methods (ОPTG, TRG). The сephalogram is used. From 175 patients resorption of roots of incisiors and canines is revealed at two patients.